Systematic meta-analyses, field synopsis and global assessment of the evidence of genetic association studies in colorectal cancer. Issue 8 (9th December 2019) - Montazeri, Zahra; Li, Xue; Nyiraneza, Christine; Ma, Xiangyu; Timofeeva, Maria; Svinti, Victoria; Meng, Xiangrui; He, Yazhou; Bo, Yacong; Morgan, Samuel; Castellví-Bel, Sergi; Ruiz-Ponte, Clara; et al.
Abstract : Objective: To provide an understanding of the role of common genetic variations in colorectal cancer (CRC) risk, we report an updated field synopsis and comprehensive assessment of evidence to catalogue all genetic markers for CRC (CRCgene2). Design: We included 869 publications after parallel literature review and extracted data for 1063 polymorphisms in 303 different genes. Meta-analyses were performed for 308 single nucleotide polymorphisms (SNPs) in 158 different genes with at least three independent studies available for analysis. Scottish, Canadian and Spanish data from genome-wide association studies (GWASs) were incorporated for the meta-analyses of 132 SNPs. To assess and classify the credibility of the associations, we applied the Venice criteria and Bayesian False-Discovery Probability (BFDP). Genetic associations classified as 'positive' and 'less-credible positive' were further validated in three large GWAS consortia conducted in populations of European origin. Results: We initially identified 18 independent variants at 16 loci that were classified as 'positive' polymorphisms for their highly credible associations with CRC risk and 59 variants at 49 loci that were classified as 'less-credible positive' SNPs; 72.2% of the 'positive' SNPs were successfully replicated in three large GWASs and the ones that were not replicated were downgraded to 'less-credible' positive (reducing the 'positive' variants to 14 at 11 loci). For the remaining 231 variants, which were previously reported, our meta-analyses found no evidence to support their associations with CRC risk. Conclusion: The CRCgene2 database provides an updated list of genetic variants related to CRC risk by using harmonised methods to assess their credibility.